Model farm services centers in Khyber Pakhtunkhwa: Evaluation and the way forward - Rana, Abdul Wajid; ul Haq, Zahoor; Iqbal, Javed; Shazad, Muhammad Faisal; Haider, Syed Zeeshan (International Food Policy Research Institute, 2023)
The sub-national Government of Khyber Pakhtunkhwa in Pakistan enacted Farm Services Centers Act, 2014, to establish Model Farm Services Centers (MFSCs) and Farm Services Centers as “one stop-shop” based on public-private partnership principle to strengthen extension system. The aim of these Centers is to empower small farmers at a platform to enhance their knowledge and skills and availability of quality agricultural inputs as stipulated in Section 4(g) of the Act, 2014, that each FSC shall “purchase certified seed, fertilizers, animal husbandry services, quality veterinary heath care services and medicines, farm machinery, expertise and technology for provision to the members who are registered with the Centre on affordable rates in comparison to open market rates”. The objective is to improve rural livelihoods, and development of the rural economy.